SOSIALISASI PELAYANAN PADA PT KRISNA HOLDING COMPANY - Opirman Waruwu (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity conducted by PT Krisna Holding Company aims to enhance the understanding and skills of the community regarding quality service. Through a series of workshops, seminars, and interactive activities, this program successfully raised awareness about the importance of good service in both social and professional contexts. The results of this activity indicate an increase in knowledge, active community engagement, and strengthened relationships between the company and the community. Thus, this initiative not only provides direct benefits to participants but also contributes to the positive reputation of PT Krisna Holding as a socially responsible company. The sustainability of this program is expected to further expand the positive impact achieved.